Chemical conversion of Calophyllum inophyllum oil into bio‐hydrocarbons fuel over presulfided NiMo/Al2O3 catalyst. (8th May 2020) - Mansur, Dieni; Aminuddin,
Summary: Chemical conversion of Calophyllum inophyllum oil (raw oil) over presulfided NiMo/Al2 O3 catalyst was conducted to generate organic liquid products (OLP) containing bio‐hydrocarbons (OLP‐1). Reacted in ±273 mL autoclave for 200 minutes at 375°C, PH2 of 1 MPa, and 1% of catalyst loading, the raw oil was converted into 78.24% OLP‐1 with a heating value of 47.93 MJ/kg. The OLP was refined through distillation and grouped into boiling point (bp) range as 13.9% of gasoline (bp at 72.6°C‐184°C), 10.8% of kerosene (bp at 184.1°C‐235°C), 47.9% of diesel oil (bp at 235.1°C‐400°C), and 26.3% of heavy fractions (bp at 400.1°C‐688.5°C). Besides OLP‐1, oxygenated compounds (OLP‐2) were also contained as by‐products. The catalytic reaction mechanism of C inophyllum oil was also confirmed using fatty acid model compounds. The OLP‐1 mainly consisted of paraffinic hydrocarbons of C10‐C18. Abstract : Chemical conversion of Calophyllum inophyllum oil over presulfided NiMo/Al2 O3 catalyst produced organic liquid products (OLP) with a heating value of 47.93 MJ/kg. OLP contained 13.9% of gasoline, 10.8% of kerosene, 47.9% of diesel oil, and 26.3% of heavy fractions. The bio‐hydrocarbon compounds containing in OLP mainly consisted of paraffinic hydrocarbons of C10 ‐C18 .